LAYANAN PENGUASAAN KONTEN UNTUK MENGATASI KESULITAN BELAJAR DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Harbeng Masni; Zuhri Saputra Hutabarat; Arif Rahim; Erlina Zahar; Ade Rahima; Heni Pratiwi; Benar Sembiring; Lili Andriani; Sujoko Sujoko; Firman Tara (LLPM Universitas Deli Sumatera, 2024)
By carrying out this community service activity, the aim is to analyze the implementation of content mastery services to help overcome student learning difficulties, and determine the application of content mastery services to improve student learning achievement. This activity method uses service actions. The subjects in this activity were 32 class XI IPS 1 students at SMAN 10 Jambi City. The data source in this activity is data obtained from respondents through observation, interviews and documents. The results of this activity found that 1) Implementation of Content Mastery Services to overcome learning difficulties and improve the learning achievement of class XI IPS 1 students at SMAN 10 Jambi City. This can be seen in the results of service activities on observation sheets, interview results and learning activities on counseling guidance material. The results of Cycle I students already understand the importance of having effective and efficient learning skills and mastery of 3M techniques. Meanwhile, in the results of cycle II, students understood and were able to demonstrate good learning behavior which was demonstrated in the form of discipline, cooperation and responsibility. This can be seen from the students' work, which is based on mutual agreement, which shows that they are able to exchange opinions, work together to solve every problem and are able to be accountable for every decision that has been mutually agreed upon.